The mediating role of emotion regulation in the relationship between parental psychological control and psychological distress among students with smartphone addiction - Xu, Liu; Arshat, Zarinah; Ismail, Nellie; Lulu, Shi (Frontiers Media SA, 2026)
Objectives: The purpose of this research was to investigate how emotion regulation, particularly reappraisal and inhibition, mediate the connection between psychological control from parents and psychological distress experienced by university students who are addicted to smartphones. Methods: A total of 1,276 university students from Henan Province, China, participated in this study. The proposed relationships and mediation pathways were examined through data analysis employing Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: Both mother psychological control (β = 0.162, p < 0.05) and father psychological control (β = 0.319, p < 0.05) were positively associated with psychological distress. Reappraisal was negatively related to psychological distress (β = -0.074, p < 0.05), whereas inhibition showed a positive correlation (β = 0.299, p < 0.05). Father psychological control was positively associated with both reappraisal (β = 0.130, p < 0.05) and inhibition (β = 0.233, p < 0.05). Mother psychological control was positively linked to inhibition (β = 0.106, p < 0.05) but not to reappraisal (β = -0.036, p > 0.05). Inhibition significantly mediated the effects of father (β = 0.070, p < 0.05) and mother psychological control (β = 0.032, p < 0.05) on psychological distress, while reappraisal did not exhibit a mediation effect. Conclusion: These findings show that inhibition mediates the psychological effects of parental psychological control on university students with smartphone addiction. These connections were not mediated by reappraisal. Interventions to reduce parental psychological control-related psychological distress should target inhibitory mechanisms, according to the study.